Navigating Identity through Cultural blending: An Autoethnographic Narrative of a Nepalese Woman's Multicultural Journey (The Journal of Nuwakot Adarsha Multiple Campus, 2025)
This article presents an autoethnographic narration of cultural blending. I have narrated my own lived experiences from my childhood to my current married life where I belong to three different ethnic groups Rai, Tamang and Newar. I have tried to explain how my identity and sense of belonging has formed and transformed across these three separate ethnic communities and their distinct culture and tradition. Through my experiences and journey, I have undertaken to relate how cultural practices, rituals, kinship structures, and belief systems are shaping and reshaping any individual and group identities. The article draws upon a few anthropological theories such as Bourdieu's habitus, Appadurai's global cultural flows, and Geertz's symbolic anthropology. The broader discussions that I have tried to bring on through my personal journey are multiculturalism, ethnicity and belonging. These concepts are explored and brought into light and discussion through cultural negotiation that I have encountered in my everyday life for example, cultural practices, kinship values etc that are evident to Rai and Tamang from my childhood days or interethnic marriage, mixing of rituals and practicing multi customs and norms in my current married life. The fluidity of identity, space and place that travels along life and experiences makes this article a meaningful anthropological study.